A novel method for sensitivity modelling of optical gas imaging thermal cameras with warm filters. Issue 5 (20th October 2022) - Olbrycht, Robert
ABSTRACT: The work proposes a novel method for sensitivity modelling of uncooled thermal cameras for optical gas imaging purposes. Such cameras use warm interference filters for better gas leak contrast at the cost of decreased sensitivity. With the presented method, it is possible to estimate this sensitivity without the need for physically installing a filter inside the camera. It can be done for any chosen background temperature and an arbitrary filter with known spectral transmission characteristic, which is often found in the filter manufacturer's documentation. The proposed method requires prior measurement of the camera calibration curve before filter installation. In addition, this method may be used for estimating, how camera noise equivalent temperature difference will change after filter installation. With the aid of new parameter gas equivalent blackbody digital level difference, one may also verify, whether in particular measurement scenario gas leak will be visible or not. The performance of the proposed method is validated with five different filters and broadband uncooled thermal imaging camera.